The CALYMHA survey: Lyα luminosity function and global escape fraction of Lyα photons at z = 2.23 - Sobral, D; Matthee, J; Best, P; Stroe, A; Röttgering, H; Oteo, I; Smail, I; Morabito, L; Paulino-Afonso, A (Oxford University Press, 2016)
We present the CAlibrating LYMan-α with Hα (CALYMHA) pilot survey and new results on Lyman α (Lyα) selected galaxies at z ∼ 2. We use a custom-built Lyα narrow-band filter at the Isaac Newton Telescope, designed to provide a matched volume coverage to the z = 2.23 Hα HiZELS survey. Here, we present the first results for the COSMOS and UDS fields. Our survey currently reaches a 3σ line flux limit of ∼4 × 10−17 erg s−1 cm−2, and a Lyα luminosity limit of ∼1042.3 erg s−1. We find 188 Lyα emitters over 7.3 × 105 Mpc3, but also find significant numbers of other line-emitting sources corresponding to He II, C III] and C IV emission lines. These sources are important contaminants, and we carefully remove them, unlike most previous studies. We find that the Lyα luminosity function at z = 2.23 is very well described by a Schechter function up to LLy α ≈ 1043 erg s−1 with L∗=10^42.59+0.16−0.08 erg s−1, ϕ∗=10^−3.09+0.14−0.34 Mpc−3 and α = −1.75 ± 0.25. Above LLy α ≈ 1043 erg s−1, the Lyα luminosity function becomes power-law like, driven by X-ray AGN. We find that Lyα-selected emitters have a high escape fraction of 37 ± 7 per cent, anticorrelated with Lyα luminosity and correlated with Lyα equivalent width. Lyα emitters have ubiquitous large (≈40 kpc) Lyα haloes, ∼2 times larger than their Hα extents. By directly comparing our Lyα and Hα luminosity functions, we find that the global/overall escape fraction of Lyα photons (within a 13 kpc radius) from the full population of star-forming galaxies is 5.1 ± 0.2 per cent at the peak of the star formation history. An extra 3.3 ± 0.3 per cent of Lyα photons likely still escape, but at larger radii.